Penentuan Prioritas Peningkatan Kualitas Pelayanan Laundry Menggunakan Metode Analytical Hierarchy Process (Studi Kasus: Smartklin Laundry) - Wandini, Ni Ketut Ayu; Sukarsa, I Komang Gde; Jayanegara, Ketut; Kencana, I Putu Eka Nila; Octavanny, Made Ayu Dwi; Tastrawati, Ni Ketut Tari (Jurnal Matematika; Vol 15 No 1 (2025), 2025)
In the competitive business world, service quality is a fundamental factor in winning the competition, especially in service industries such as laundry. Improving service quality requires proper allocation of resources, particularly when faced with cost limitations. This study aims to analyze and determine priority alternatives for improving laundry service quality based on customer preferences at SmartKlin Laundry using the Analytical Hierarchy Process (AHP) method. Data in this study uses primary data obtained from 10 respondents through purposive sampling techniques. The results show that the Assurance criterion (0,349) is the top priority, followed by Reliability (0,275), Responsiveness (0,187), Empathy (0,122), and Tangible (0,067). The top priority alternative is employee training (0.550), followed by the implementation of a loyalty program (0,303), and the purchase of laundry equipment (0,146). These findings indicate the importance of improving employee quality through training and loyalty programs to enhance customer satisfaction and the competitiveness of SmartKlin Laundry .